PENGENALAN TEKNOLOGI WEBSITE UNTUK MENINGKATKAN KETERAMPILAN DIGITAL SANTRI PESANTREN NAFIDATUNNAJAH RAWAKALONG, KEC. GUNUNG SINDUR, KABUPATEN BOGOR - Sri Rama Putri; Nurhayati; Sunandar, Dede (JAMAIKA: JURNAL ABDI MASYARAKAT, 2026)
Advances in information technology have brought significant changes to human life, including in the world of Islamic education. One example of this progress is the emergence of websites as digital media, which have now become an essential part of daily activities. In Indonesia, with more than 220 million internet users (APJII, 2024), the digital world is developing rapidly. However, this increase in user numbers has not been accompanied by adequate digital literacy skills, especially among Islamic boarding school students. Nafidatunnajah Islamic Boarding School in Rawakalong Village, Gunung Sindur District, Bogor Regency, is one of the Islamic educational institutions that still uses traditional methods in teaching and learning. While these values ​​and traditions are important to maintain, modern developments require Islamic boarding schools to balance religious education with digital skills. To date, most students have not received training in technology, particularly website management. Yet, websites have great potential to be used as a means of preaching, publishing activities, and digital-based learning. Through websites, Islamic boarding schools can introduce their institutions, broadcast activities, and disseminate Islamic values ​​more widely. Unfortunately, there are several obstacles such as a lack of computer and internet facilities, a lack of educators who understand information technology, and a low awareness of the importance of digital skills in Islamic boarding schools. This program aims to improve the digital skills of students through an introduction to basic website concepts, the practice of creating simple web pages, and an understanding of the ethics of using technology according to Islamic values. This activity is expected to broaden the students' horizons that technology is not a threat, but rather a tool that can be used to strengthen da'wah, spread knowledge, and increase the competitiveness of the Islamic boarding school generation. Keywords: Globalization Era, Islamic Boarding Schools, Websites